Continuous spike-waves during slow waves sleep: a clinical and electroencephalografic study in fifteen children - ADRIANA A. F. DJABRAIAN; MARCUS SABRY AZAR BATISTA; MÁRCIA M. DE LIMA; DÉLRIO FAÇANHA SILVA (Arquivos de Neuro-Psiquiatria)
We report on the clinical and EEG features of 15 patients with the syndrome of "continuous spike waves during slow wave sleep" (CSWSS). The differential diagnosis of CSWSS includes benign epilepsy of childhood with centro-temporal spikes, and Landau-Kleffner and Lennox-Gastaut syndromes. We found normal CT and MRI features in 6 cases, periventricular leukomalacia with and without diffuse brain atrophy in 4 cases and hydrocephalus in 1 case. There was no association between specific neurological findings and CSWSS. Nine of our cases had relatively focal discharges, like some cases from the literature. The occurrence of CSWSS appears to be age-related, generaly between the ages of 5 to 12 years, with a strong temporal relation to the neupsychological deterioration in its nature, severity and prognosis. We believe that this striking disorder has been overlooked and that routine sleep EEG studies on epileptic children may disclose additional cases of CSWSS.